Learning Tahfidz Quran Method in North Lintau Buo Subdistrict Flat Land District - Rahmat Akmal (Program Pascasarjana UMSB, 2021)
This study aims to describe the method of learning tahfidz al-Qur'an used by teachers in Lintau Buo Utara Subdistrict, Tanah Datar Regency, Students feel bored and bored with the learning methods conducted by teachers and students talk to each other so that students pay less attention to teachers when explaining. This research method is a qualitative type of research. The results of the study showed that teachers in conducting learning tahfidz al-Qur'an in Lintau Buo Utara Subdistrict Tanah Datar district using varied methods such as talaqqi method, verse method per verse, method 5 paragraph 5 verses, takrir method and al-jawarih method so that students are excited, diligent, not bored and not saturated in following the learning tahfidz al-Qur'an in Lintau Buo Utara Subdistrict with the method used by teachers.